## Trending News

Promoted

# the expression 2a^-2b^3 is equivalent to?

Update:

i no the answer but i just need the work. Can you show how you get the answer

### 5 Answers

Relevance

- Anonymous6 years agoFavorite Answer
Here, you are making the exponent of 'a' positive.

So you would use: x^-n = 1/x^n, so...

2a^-2 b^3

2b^3 * a^-2

2b^3 * 1/a^2

(2b^3)/(a^2) <--- answer

- How do you think about the answers? You can sign in to vote the answer.
- Fazaldin ALv 76 years ago
2a^-2b^3 = 2 / a^2b^3 >==============< ANSWER

OR,

2a^-2b^3 = 2b^3 / a^2 >==============< ANSWER

Still have questions? Get your answers by asking now.